CAA2016 : oceans of data : proceedings of the 44th Conference on Computer Applications and Quantitative Methods in Archaeology /: oceans of data : proceedings of the 44th Conference on Computer Applications and Quantitative Methods in Archaeology. (2018) - Unknown
No abstract available